2006
DOI: 10.1002/pen.20503
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of highly transparent polypropylene cast films: Influence of material structure, additives, and processing conditions

Abstract: Polypropylene homopolymers and ethylene/propylene-random-copolymers formulated with and without anti-blocking additives were extruded to cast films with an industrial scale extruder equipped with a soft box, a specific air knife that expels a higher volume of air at lower velocity. The films were analyzed as to their optical properties haze and clarity. A comprehensive topographical characterization was performed using atomic force microscopy (AFM) and confocal microscopy. To obtain morphological information o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…PP cast film studies are closely related to the formation and stability of mesomorphic phase as a result of the high cooling rates in this specific process. This has been recognized already by Geil et al, while later studies confirmed the importance of processing parameters for optical and mechanical performance . A systematic modelling of the crystallization during processing is desired for understanding the connection between processing and final properties .…”
Section: Processing‐based Modificationsmentioning
confidence: 73%
“…PP cast film studies are closely related to the formation and stability of mesomorphic phase as a result of the high cooling rates in this specific process. This has been recognized already by Geil et al, while later studies confirmed the importance of processing parameters for optical and mechanical performance . A systematic modelling of the crystallization during processing is desired for understanding the connection between processing and final properties .…”
Section: Processing‐based Modificationsmentioning
confidence: 73%
“…The main difference between the crystallization processes in injection molding is that in this process besides the "classical" nucleation shear-induced crystallization can occur whereas in the blown film process besides the nucleation an orientation/elongation process happens. Another important aspect for films is the predominant role of surface roughness, which has been nicely demonstrated for the case of PP cast films (Resch et al, 2006;.…”
Section: Optical Effectsmentioning
confidence: 97%
“…Molecular and other physical properties are listed in Table 1. RACO2 differs from the iPP and the other two RACO's in that it contains some additives not present in the others like a slip agent to reduce the friction coefficient (for post-processing steps in film applications) and a synthetic silica anti-blocking aid to reduce the adhesion between the film layers [32,33]. The anti-blocking aid consists of both spherical and plate-like particles ranging in size between 100 nm up to 10 lm.…”
Section: Methodsmentioning
confidence: 99%